2004
DOI: 10.1200/jco.2004.08.159
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of High-Risk Stage IC, Grade 3, Compared With Stage I Endometrial Carcinoma Patients: The Postoperative Radiation Therapy in Endometrial Carcinoma Trial

Abstract: Patients with stage IC, grade 3 endometrial carcinoma are at high risk of early distant spread and endometrial carcinoma-related death. Novel strategies for adjuvant therapy should be explored to improve survival for this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(129 citation statements)
references
References 30 publications
3
122
1
3
Order By: Relevance
“…The Post Operative Radiation Therapy in Endometrial Carcinoma (PORTEC) trial reported 5-year survival rates for patients with stage IB G2, IB G3, IC G1, IC G2, and IC G3 disease of 86%, 74%, 83%, 85%, and 58%, respectively. 3 Therefore, it is important to keep in mind that prognoses can differ dramatically across subgroups within stage I.…”
Section: Discussionmentioning
confidence: 99%
“…The Post Operative Radiation Therapy in Endometrial Carcinoma (PORTEC) trial reported 5-year survival rates for patients with stage IB G2, IB G3, IC G1, IC G2, and IC G3 disease of 86%, 74%, 83%, 85%, and 58%, respectively. 3 Therefore, it is important to keep in mind that prognoses can differ dramatically across subgroups within stage I.…”
Section: Discussionmentioning
confidence: 99%
“…Although this neoplasm is generally considered non-aggressive, it is a heterogeneous disease with 5-year survival rates ranging from over 80 -90% for women with clinical stage I disease (Creutzberg et al, 2004). Currently, various clinicopathologic parameters are used to predict the outcome of the disease and to decide the need for adjuvant treatment: surgical stage, histological type, grade, depth of myometrial invasion, cervical stromal invasion, lymph node metastasis, lymph vascular involvement, and peritoneal cytology (Morrow et al, 1991;Grigsby et al, 1992); however, the majority of parameters have been criticised for their subjectivity and poor reproducibility (Nordstrom et al, 1996).…”
mentioning
confidence: 99%
“…15 The overall survival at 5 years was 58% for the IC grade 3 patients, compared to 74% for those with IB grade 3, and 83-86% for IB grade 2 and IC grade 1 and 2 disease (p<0.001).…”
Section: Pagementioning
confidence: 91%